Composite molecular sieve as well as preparation method and application thereof
By adding persulfate to the synthetic system and crystallizing the initial gel mixture containing phosphorus source, silicon source, aluminum source and template agent in the presence, the problem of the inability to directly synthesize the CHA and AFN structure composite molecular sieve in the prior art is solved, and the synthesis of composite molecular sieve with high crystallinity and large micropore specific surface area is achieved, with a wide range of catalytic and gas adsorption application prospects.
Patent Information
- Application Number
- CN202311334872.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-16
AI Technical Summary
The prior art cannot directly synthesize composite molecular sieves with CHA structure and AFN structure, and the preparation method is cumbersome.
Persulfate was added to the synthetic system, and the initial gel mixture containing a phosphorus source, silicon source, aluminum source, template agent and water was crystallized. The template agent was an organic amine with no more than 3 carbon atoms.
The direct synthesis of composite molecular sieve with CHA structure and AFN structure has high crystallinity, a large micropore specific surface area and micropore volume, and is suitable for acid catalytic reactions and gas adsorption.
Smart Images

Figure CN119841330A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic material synthesis, and in particular to a composite molecular sieve having a CHA structure and an AFN structure, and a preparation method and application thereof. Background Art
[0002] Composite molecular sieve is a composite molecular sieve with a special structure. It is a co-crystal formed by two or more molecular sieves, or a composite crystal with the structural characteristics of two or more molecular sieves. Due to the particularity of the composite molecular sieve structure, this molecular sieve has a more reasonably distributed pore structure, acidity and other properties, overcoming the limitations of a single molecular sieve, and can better meet the needs of applications such as catalysis, and has broad application prospects.
[0003] AFN molecular sieve belongs to the triclinic system, the space group is P-1, and the unit cell parameters are α=77.81°,β=77.50°,γ=87.69°,with a three-dimensional 8-membered ring channel structure, the 8-membered ring pore size along the
[100] direction is 0.19×0.46nm, the 8-membered ring pore size along the
[010] direction is 0.21×0.49nm, and the 8-membered ring pore size along the
[001] direction is 0.33×0.4nm, belonging to a small pore molecular sieve. CHA structure molecular sieve belongs to the trigonal crystal system, the space group is R-3m, the unit cell parameters α=94.47°,β=94.47°,γ=94.47°,it has an eight-membered ring ellipsoidal cage (cha cage) formed by stacking double six-membered rings in ABC manner and a three-dimensional cross-channel structure, with a pore size of 0.38nm×0.38nm and a cage size of 1.0nm×0.67nm×0.67nm, and is a small-pore molecular sieve.
[0004] CN114054081A reports a SAPO-34 / SAPO-14 composite molecular sieve and its preparation method and application. It needs to add seed crystals and undergo two crystallizations for synthesis. SAPO-34 molecular sieve seed crystals are first prepared through a process of primary crystallization, filtration, water washing, drying, etc., and then the SAPO-34 molecular sieve seed crystals are added to a SAPO-14 molecular sieve synthesis gel system for secondary crystallization, filtration, water washing, drying, etc. The preparation method is cumbersome. Summary of the invention
[0005] In view of the shortcomings of the existing preparation technology of composite molecular sieves with CHA structure and AFN structure, the purpose of the present invention is to provide a simple and convenient composite molecular sieve for direct synthesis of CHA structure and AFN structure and a preparation method and application thereof.
[0006] The inventors of the present invention have found that by adding persulfate to the synthesis system for synthesis, a composite molecular sieve having a CHA structure and an AFN structure can be obtained, which solves the problem that the prior art cannot directly synthesize a composite molecular sieve having a CHA structure and an AFN structure. Therefore, the present invention provides a method for preparing a composite molecular sieve having a CHA structure and an AFN structure, the preparation method comprising: crystallizing an initial gel mixture containing a phosphorus source, a silicon source, an aluminum source, a template and water in the presence of persulfate, wherein the template is an organic amine having a carbon number not exceeding 3.
[0007] The present invention also provides a composite molecular sieve having a CHA structure and an AFN structure and application thereof.
[0008] The present invention can obtain a composite molecular sieve with a CHA structure and an AFN structure, which has high crystallinity, a large micropore specific surface area and a micropore volume, has potential application prospects in the fields of acid catalytic reaction and gas adsorption, and has a simple synthesis method, thereby solving the problem that the prior art cannot directly synthesize a composite molecular sieve with a CHA structure and an AFN structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 XRD spectrum of the molecular sieve sample synthesized in Example 1;
[0010] Figure 2 XRD spectrum of the molecular sieve sample synthesized in Example 2;
[0011] Figure 3 This is the XRD spectrum of the molecular sieve sample synthesized in Example 3. DETAILED DESCRIPTION
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0013] The present invention provides a method for preparing a composite molecular sieve having a CHA structure and an AFN structure, characterized in that the preparation method comprises: crystallizing an initial gel mixture containing a phosphorus source, a silicon source, an aluminum source, a template and water in the presence of persulfate, wherein the template is an organic amine having a carbon atom number not exceeding 3.
[0014] In the initial gel mixture of the present invention, the molar ratio of the phosphorus source to the aluminum source can be 0.6-1.22:1, preferably 0.8-1.2:1 (such as 0.9, 0.95, 0.98, 0.99, 1, 1.1, 1.2 or any value in between).
[0015] In the initial gel mixture of the present invention, the molar ratio of the silicon source to the aluminum source can be 0.01-1:1, preferably 0.1-0.9:1 (such as 0.3, 0.35, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or any value therebetween).
[0016] In the initial gel mixture of the present invention, the molar ratio of the template to the aluminum source can be 1-10:1, preferably 1.1-5:1 (such as 1.1, 1.5, 2, 3, 4, 5 or any value in between).
[0017] In the initial gel mixture of the present invention, the molar ratio of water to aluminum source can be 10-200:1, preferably 12-80:1 (such as 15, 20, 30, 40, 50, 60, 70, 80 or any value therebetween).
[0018] In the initial gel mixture of the present invention, the molar ratio of persulfate to aluminum source can be 0.001-0.02:1, preferably 0.002-0.018:1 (such as 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.01, 0.013, 0.014, 0.017, 0.018 or any value therebetween).
[0019] In the present invention, the phosphorus source is calculated as P2O5, the aluminum source is calculated as Al2O3, and the silicon source is calculated as SiO2.
[0020] In the present invention, the persulfate radical can be provided by various substances capable of providing persulfate radicals in the initial gel mixture, preferably by alkali metal persulfate, more preferably by sodium persulfate and / or potassium persulfate.
[0021] In the present invention, the phosphorus source and the aluminum source can be substances that are common in the art and can provide P and / or Al. According to a preferred embodiment of the present invention, the phosphorus source and the aluminum source are provided by a phosphorus-aluminum complex. The molar ratio of P in terms of P2O5 to Al in terms of Al2O3 in the phosphorus-aluminum complex is 0.8-1.2, and the phosphorus-aluminum complex has a phosphorus-aluminum crystal skeleton structure. The phosphorus-aluminum complex can be prepared by referring to the method described in CN111422843A. The phosphorus-aluminum complex is used as a phosphorus source and an aluminum source to synthesize the composite molecular sieve of the present invention, which has low cost, good repeatability, high crystallinity of the molecular sieve product, and can be synthesized under conditions of a lower water-aluminum ratio, thereby improving the problems of low single-pot yield and high wastewater discharge caused by the high water-aluminum ratio in traditional hydrothermal synthesis.
[0022] According to another preferred embodiment of the present invention, the phosphorus source and the aluminum source are provided by different substances. For example, the phosphorus source may be phosphoric acid, preferably orthophosphoric acid; the aluminum source may be aluminum oxide and / or aluminum hydroxide, preferably at least one of anhydrous aluminum oxide, aluminum hydroxide and pseudo-boehmite.
[0023] In the present invention, the silicon source may be a substance commonly used in the art that can provide Si, for example, the silicon source may be silicon dioxide, preferably white carbon black and / or silica gel.
[0024] According to a preferred embodiment of the present invention, the template (or structure directing agent) is an alkylamine having a carbon number not exceeding 3, more preferably isopropylamine. Using isopropylamine as a template can be more conducive to the synthesis of composite molecular sieves having CHA structure and AFN structure.
[0025] In the present invention, there is no special requirement for the crystallization method. One-stage crystallization can be adopted, and the one-stage crystallization method can be: crystallization at 170-205°C for 20-80 hours; two-stage crystallization can also be adopted. In a preferred embodiment of the present invention, the crystallization includes sequentially performing a first stage crystallization and a second stage crystallization, and the temperature of the first stage crystallization is lower than the temperature of the second stage crystallization. More preferably, the temperature of the first stage crystallization is 25-55°C lower than the temperature of the second stage crystallization (such as 26, 28, 32, 35, 38, 42, 45, 48, 52, 54°C or any value between the above values). More preferably, the time of the first stage crystallization is 5-10h shorter than the time of the second stage crystallization (such as 5.2, 5.8, 6.2, 6.5, 6.8, 7.2, 8.5, 9.8h or any value between the above values).
[0026] More preferably, the conditions for the first stage of crystallization include: a temperature of 140-160° C. (such as 141, 142, 145, 148, 152, 155, 158, 159° C. or any value therebetween). More preferably, the conditions for the first stage of crystallization also include: a time of 33-40 h (such as 34, 35, 36, 37, 38, 39, 40 h or any value therebetween).
[0027] More preferably, the conditions for the second stage of crystallization include: a temperature of 170-190° C. (such as 175, 176, 178, 180, 182, 184, 185, 189° C. or any value therebetween). More preferably, the conditions for the second stage of crystallization also include: a time of 25-50 h (such as 27, 29, 40, 41, 43, 45, 47, 49, 50, 52, 54 h or any value therebetween).
[0028] In the present invention, the crystallization has no special requirements on the pressure, and can be autogenous pressure. The crystallization can be static crystallization or dynamic crystallization, preferably dynamic crystallization. As a condition for dynamic crystallization, the preferred rotation speed is 15-40r / min.
[0029] According to a more preferred embodiment of the present invention, the first stage of crystallization is carried out at autogenous pressure and 145-155° C. for 35-39 hours, and the second stage of crystallization is carried out at autogenous pressure and 175-185° C. for 30-45 hours.
[0030] In the present invention, in order to obtain a molecular sieve (raw powder), the method may further include subjecting the crystallized product to solid-liquid separation, and then washing, drying and optionally calcining the obtained solid phase in sequence to obtain a molecular sieve. Specifically, the solid-liquid separation method can be carried out by conventional methods, such as filtering, centrifugal separation, etc. In addition, the solid phase obtained by solid-liquid separation is washed before drying. The washing can be carried out by conventional methods, and in order to avoid the introduction of other impurities, it is preferably washed with deionized water to neutrality. The drying can be carried out at a temperature of 70-110°C, and the drying time can be selected according to the drying temperature, generally 4-12 hours. The calcination temperature can be 500-600°C, and the calcination time can be 3-5h.
[0031] The present invention also provides a composite molecular sieve having a CHA structure and an AFN structure, characterized in that the composite molecular sieve is prepared by the method as described above;
[0032] Alternatively, the weight percentage of the CHA structure molecular sieve in the composite molecular sieve is 10-95% (preferably 70-78%), and the weight percentage of the AFN structure molecular sieve is 5-90% (preferably 22-30%).
[0033] According to the present invention, the anhydrous chemical composition of the composite molecular sieve is (SixAlyPz)O2, x, y, z represent the molar fractions of Si, Al, and P, respectively, and their value ranges are x=0.01-0.2 (preferably equal to 0.05-0.07), y=0.3-0.49 (preferably equal to 0.4-0.45), z=0.4-0.6 (preferably equal to 0.5-0.55), and x+y+z=1; and the weight percentage of Na2O is 0-0.3%, preferably 0.05-0.2%.
[0034] According to the present invention, the micropore specific surface area of the composite molecular sieve is not less than 340m 2 / g, preferably 350-400m 2 / g.
[0035] According to the present invention, the micropore volume of the composite molecular sieve is not less than 0.155 cm 3 / g, preferably 0.16-0.18cm 3 / g.
[0036] In addition, the present invention also provides the use of the composite molecular sieve as a catalyst in an acid-catalyzed reaction, wherein the acid-catalyzed reaction is preferably a reaction of converting oxygen-containing compounds (such as alcohols, preferably methanol) into olefins or a linear alkane isomerization reaction.
[0037] The present invention also provides the use of the composite molecular sieve as described above in gas adsorption treatment.
[0038] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0039] X-ray powder diffraction (XRD) was performed using a PANalytical Empyrean diffractometer equipped with a PIXcel 3D Detector. Test conditions: Cu target, Kα radiation, Ni filter, tube voltage 40kV, tube current 40mA, scanning range 5°-50°. The weight percentage of molecular sieves with different physical phase structures in the composite molecular sieve is determined according to the characteristic peaks of each molecular sieve in the XRD spectrum, that is, the weight percentage of each phase is calculated according to the peak height of the unique characteristic peak of the highest intensity of each molecular sieve. The specific calculation method is as follows: the highest intensity characteristic peaks of CHA structure molecular sieve are 9.4°, and the characteristic peaks of AFN structure molecular sieve are 8.9°. The peak heights of the characteristic peaks of CHA structure molecular sieve and AFN structure molecular sieve are recorded as S1 and S2 respectively; the weight percentage of CHA structure molecular sieve in the composite molecular sieve = S1 / (S1+S2)×100%; the weight percentage of AFN structure molecular sieve = S2 / (S1+S2)×100%.
[0040] The inorganic element composition analysis (XRF) of the molecular sieve samples was carried out using a Philips MagiX fluorescence spectrometer.
[0041] The test instrument for BET analysis is Micromeritics ASAP 2010 adsorption instrument. Test conditions: The weighed sample is vacuumed to 1.33×10 -2 Pa, constant temperature and pressure for 15 hours, sample pretreatment. At liquid nitrogen temperature -196 ° C, the sample's nitrogen adsorption and desorption under different pressure ratios p / p0 were measured to obtain nitrogen adsorption-desorption isotherms. The t-plot method was used to calculate the micropore specific surface area and micropore volume of the sample.
[0042] In the following examples, R represents an organic template: isopropylamine.
[0043] The examples are used to illustrate the synthesis of the composite molecular sieves having CHA structure and AFN structure described in the present invention.
[0044] Example 1
[0045] Crystalline aluminum phosphate was prepared according to the method described in Example 2 of CN111422843A, with a solid content of 100% and P2O5 / Al2O3=0.99 (molar ratio).
[0046] Take 10.999 grams of deionized water and add it to the polytetrafluoroethylene liner, add isopropylamine (mass fraction 99%), then add crystalline aluminum phosphate, then add solid silica gel (mass fraction 93.3%), stir and mix evenly. Add sodium persulfate (mass fraction 99%) to 7g of water, stir to dissolve, and add it to the above mixture, stir and mix evenly. The added molar ratio of each component is: P2O5 / Al2O3=0.99, SiO2 / Al2O3=0.3, R / Al2O3=2, H2O / Al2O3=40, Na2S2O8 / Al2O3=0.004.
[0047] The polytetrafluoroethylene liner containing the above reaction mixture was covered, placed in a stainless steel autoclave and sealed, and placed in a rotary convection oven with a rotation speed set to 20 r / min. Crystallization was carried out under autogenous pressure: crystallization at 150°C for 36 hours and at 180°C for 45 hours. After the crystallization was completed, the temperature was lowered to room temperature, the product was taken out, filtered, washed, and dried at 110°C for 12 hours to obtain a solid powder sample.
[0048] The obtained solid powder sample was subjected to X-ray diffraction analysis, and the XRD spectrum is shown in Figure 1, referring to the XRD spectra of CHA structure in CN107915237B and the XRD spectra of AFN structure in CN112624137B, it is confirmed that the obtained solid powder sample is a composite molecular sieve with CHA structure and AFN structure. The weight percentage of CHA structure molecular sieve in the composite molecular sieve is 73.67%, and the weight percentage of AFN structure molecular sieve is 26.33%. The obtained composite molecular sieve is subjected to XRF element analysis, and its chemical composition is (Si 0.07 Al 0.42 P 0.51 )O2, of which the weight percentage of Na2O is 0.0681%. The obtained composite molecular sieve was calcined at 550℃ for 3h and subjected to BET analysis. Its micropore specific surface area is 351m 2 / g, micropore volume is 0.162cm 3 / g, the obtained composite molecular sieve has good micropore specific surface area and micropore volume, indicating that the crystal structure of the composite molecular sieve is complete and the crystallinity is high.
[0049] Example 2
[0050] The preparation method of Example 1 is followed, except that the added molar ratios of the components are: P2O5 / Al2O3=0.99, SiO2 / Al2O3=0.35, R / Al2O3=3, H2O / Al2O3=60, Na2S2O8 / Al2O3=0.007.
[0051] The obtained solid powder sample was subjected to X-ray diffraction analysis, and the XRD spectrum is shown in Figure 2 , which is a composite molecular sieve with CHA structure and AFN structure. XRD diffraction quantitatively shows that the weight percentage of CHA structure molecular sieve in the composite molecular sieve is 73.01%, and the weight percentage of AFN structure molecular sieve is 26.99%. The obtained composite molecular sieve is subjected to XRF element analysis, and its chemical composition is (Si 0.06 Al 0.44 P 0.50 )O2, of which the weight percentage of Na2O is 0.0912%. The obtained composite molecular sieve was calcined at 550℃ for 3h and subjected to BET analysis. Its micropore specific surface area is 364m 2 / g, micropore volume is 0.169cm 3 / g, the obtained composite molecular sieve has good micropore specific surface area and micropore volume, indicating that the crystal structure of the composite molecular sieve is complete and the crystallinity is high.
[0052] Example 3
[0053] The preparation method is the same as in Example 1, except that Na2S2O8 / Al2O3=0.014.
[0054] The obtained solid powder sample was subjected to X-ray diffraction analysis, and the XRD spectrum is shown in Figure 3 , which is a composite molecular sieve with CHA structure and AFN structure. XRD diffraction quantitatively shows that the weight percentage of CHA structure molecular sieve in the composite molecular sieve is 76.3%, and the weight percentage of AFN structure molecular sieve is 23.7%. The obtained molecular sieve raw powder sample was subjected to XRF element analysis, and its chemical composition is (Si 0.06 Al 0.42 P 0.52 )O2, of which the weight percentage of Na2O is 0.174%. The obtained composite molecular sieve was calcined at 550℃ for 3h and subjected to BET analysis. Its micropore specific surface area is 357m 2 / g, micropore volume is 0.165cm 3 / g, the obtained composite molecular sieve has good micropore specific surface area and micropore volume, indicating that the crystal structure of the composite molecular sieve is complete and the crystallinity is high.
[0055] Example 4
[0056] The preparation method of Example 2 was followed, except that phosphoric acid was added as a phosphorus source and pseudo-boehmite was added as an aluminum source. The obtained solid powder sample was subjected to X-ray diffraction analysis, which showed that it was a composite molecular sieve having a CHA structure and an AFN structure.
[0057] Comparative Example 1
[0058] The preparation method of Example 2 was followed, except that isopropylamine was not added, but the same amount of isobutylamine was added as a template. The obtained solid powder sample was subjected to X-ray diffraction analysis, which showed that it was other molecular sieve crystal phases, and did not contain CHA structure and AFN structure.
[0059] Comparative Example 2
[0060] The preparation method of Example 2 was followed, except that sodium persulfate was not added. The obtained solid powder sample was subjected to X-ray diffraction analysis, which showed that it was an AFN structure molecular sieve.
[0061] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0062] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0063] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a composite molecular sieve having a CHA structure and an AFN structure, characterized in that: The synthesis method comprises: crystallizing an initial gel mixture containing a phosphorus source, a silicon source, an aluminum source, a template agent and water in the presence of persulfate, wherein the template agent is an organic amine with a carbon number not exceeding 3.
2. The preparation method according to claim 1, wherein In the initial gel mixture, the molar ratio of phosphorus source, silicon source, aluminum source, template, water and persulfate is 0.6-1.22:0.01-1:1:1-10:10-200:0.001-0.02, preferably 0.8-1.2:0.1-0.9:1:1.1-5:12-80:0.002-0.018, wherein the phosphorus source is calculated as P2O5, the aluminum source is calculated as Al2O3, and the silicon source is calculated as SiO2.
3. The preparation method according to claim 1 or 2, wherein The persulfate is provided by an alkali metal persulfate, preferably sodium persulfate and / or potassium persulfate.
4. The preparation method according to claim 1 or 2, wherein: The phosphorus source and the aluminum source are provided by a phosphorus-aluminum complex, in which the molar ratio of P calculated as P2O5 to Al calculated as Al2O3 is 0.8-1.2, and the phosphorus-aluminum complex has a phosphorus-aluminum crystal framework structure.
5. The preparation method according to claim 1 or 2, wherein: The phosphorus source is phosphoric acid, preferably orthophosphoric acid; And / or, the silicon source is silicon dioxide, preferably white carbon black and / or silica gel; And / or, the aluminum source is aluminum oxide and / or aluminum hydroxide, preferably at least one of anhydrous aluminum oxide, aluminum hydroxide and pseudo-boehmite; And / or, the template agent is isopropylamine.
6. The preparation method according to claim 1 or 2, wherein: The crystallization includes sequentially performing a first stage crystallization and a second stage crystallization, wherein the temperature of the first stage crystallization is lower than the temperature of the second stage crystallization; Preferably, the first stage of crystallization is carried out at autogenous pressure and 140-160° C. for 33-40 hours, and the second stage of crystallization is carried out at autogenous pressure and 170-190° C. for 25-50 hours; More preferably, the first stage of crystallization is carried out at autogenous pressure and 145-155° C. for 35-39 hours, and the second stage of crystallization is carried out at autogenous pressure and 175-185° C. for 30-45 hours.
7. The preparation method according to claim 1 or 2, wherein: The crystallization method is: crystallization at 170-205° C. for 20-80 hours.
8. The preparation method according to claim 1 or 2, wherein: The method further comprises: sequentially performing solid-liquid separation, washing, drying and optional calcination on the crystallized product.
9. The preparation method according to claim 8, wherein: The drying temperature is 70-110°C, and the drying time is 4-12h; And / or, the calcination temperature is 500-600° C., and the calcination time is 3-5 hours.
10. A composite molecular sieve having a CHA structure and an AFN structure, characterized in that: The composite molecular sieve is prepared by the preparation method described in any one of claims 1 to 9; Alternatively, the weight percentage of the CHA structure molecular sieve in the composite molecular sieve is 10-95%, and the weight percentage of the AFN structure molecular sieve is 5-90%.
11. The composite molecular sieve according to claim 10, wherein: The anhydrous chemical composition of the composite molecular sieve is (SixAlyPz)O2, x, y, z represent the molar fractions of Si, Al, and P, respectively, and the value ranges are x=0.01-0.2, y=0.3-0.49, z=0.4-0.6, and x+y+z=1; and the weight percentage of Na2O is 0-0.3%; And / or, the micropore specific surface area of the composite molecular sieve is not less than 340m 2 / g, preferably 350-400m 2 / g; And / or, the micropore volume of the composite molecular sieve is not less than 0.155cm 3 / g, preferably 0.16-0.18cm 3 / g.
12. Use of the composite molecular sieve according to claim 10 or 11 as a catalyst in an acid-catalyzed reaction; preferably, the acid-catalyzed reaction is a reaction of converting oxygen-containing compounds to olefins or a linear alkane isomerization reaction.
13. Use of the composite molecular sieve according to claim 10 or 11 in gas adsorption treatment.
Citation Information
Patent Citations
A twinned SAPO-34 molecular sieve, its synthesis method, and a method for methanol-to-olefins.
CN107915237B
Molecular sieve synthesis method
CN111422843A
AFN-structured molecular sieves composed of cobalt, phosphorus, and aluminum, their synthesis methods and applications
CN112624137B
AFN structure silicon-phosphorus-aluminum molecular sieve, as well as preparation method and application thereof
CN108147423A
SAPO-34 / SAPO-14 composite molecular sieve as well as preparation method and application thereof
CN114054081A